Reframing African Girlhood. Issue 1 (1st March 2023) - Mitchell, Claudia
Abstract : This Special Issue on African Girlhoods is long overdue for many reasons, not least of which is its recognition, as guest editors Marla L. Jaksch, Catherine Cymone Fourshey, and Relebohile Moletsane point out, of the somewhat vexed history of the discourse of the African girl-child that dates back to the global development literature of the early 1990s attached to the Fourth World Conference on Women: Action for Equality, Development and Peace, held in Beijing in September, 1995—typically referred to just as Beijing. This, and the many country and regional conferences leading up it were (and still are) game-changers in so many ways when it comes to the lives of girls and women. It would be remiss of me not to acknowledge that I participated readily in the early days of defining the girl-child when I was working as a short-term UNICEF consultant in Zambia to develop an agenda for the Ministry of Education and other policy actors for research about education for girls in Zambia. One of the events in which I participated in Lusaka in October 1994 as part of my fact-finding and local consulting was a meeting of 80 or more local NGO members and other Zambian women who were planning their submissions to the November 1994 African Platform for Action: Fifth African Regional Conference (Dakar) on Women preparatory to Beijing. As an observer at this meeting, I heard a presenter talk about the fact that she was one of the first women (if not the first) in Zambia to graduate from university. This was in 1994 and at the time I could see that giving any recognition and support to ordinary girls and their education was full of possibilities, if very complicated. But I regard all this as just as much a part of the development of Girlhood Studies as was the work in North America on girls and science in the late 1980s. As I note elsewhere on charting girlhood studies (Mitchell 2016) we now know that just getting more girls into science was equally complicated.